2015
DOI: 10.1155/2015/916971
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofGBAMutations on Phenotype of Parkinson’s Disease: A Study on Chinese Population and aMeta-Analysis

Abstract: GBA has been identified as a genetic risk factor for PD. Whether the clinical manifestations of PD patients with or without GBA mutations are different has still not reached a consensus. We firstly detected the GBA mutation L444P in 1147 Chinese PD patients and simultaneously evaluated their corresponding clinical data. Then we compared the phenotypes between 646 PD patients with GBA mutations and 10344 PD patients without GBA mutations worldwide through meta-analysis. Through the method of meta-analysis, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 30 publications
(20 reference statements)
3
44
0
Order By: Relevance
“…GBA1 heterozygotes have an earlier age at onset compared with noncarriers of 3‐6 years for PD and 5‐7 years for DLB, respectively. Mean age at onset in heterozygous PD carriers is about 50‐55 years . Among GBA1 carriers who develop PD, homozygotes have a 6‐ to 11‐year earlier onset than heterozygotes .…”
Section: Clinical and Neuroimaging Features Of Gba‐related Synucleinomentioning
confidence: 99%
See 1 more Smart Citation
“…GBA1 heterozygotes have an earlier age at onset compared with noncarriers of 3‐6 years for PD and 5‐7 years for DLB, respectively. Mean age at onset in heterozygous PD carriers is about 50‐55 years . Among GBA1 carriers who develop PD, homozygotes have a 6‐ to 11‐year earlier onset than heterozygotes .…”
Section: Clinical and Neuroimaging Features Of Gba‐related Synucleinomentioning
confidence: 99%
“…52,53 Nonetheless, as the 2 prospective studies to date were performed among family members of GD cases, 52,53 the actual penetrance of GBA1 mutations in the general population remains to be established conclusively. A positive familial history can be identified in 21.5%-31% of PD carriers of GBA1 mutations, 6,47,49,54 suggesting that more than two-thirds of PD carriers of GBA1 mutations are sporadic. The agespecific risk for PD among homozygotes is not significantly different from heterozygotes, being 4.7% by age 60 years and 9.1% by age 80 years.…”
Section: Clinical and Neuroimaging Features Of Gba-related Synucleinomentioning
confidence: 99%
“…No difference was observed in tremor and dyskinesia between GBA and idiopathic cases in one series [49], although a large European series reported that levodopa induced dyskinesia was more severe in PD with GBA mutations than with controls [48]. Severity of the GBA mutation in terms of its effect on enzyme activity, is associated with earlier age of onset [48,50].…”
Section: Motor Featuresmentioning
confidence: 84%
“…Studies of the presenting motor features in GBA associated PD demonstrated that bradykinesia is a more common initial symptom compared with idiopathic cases and that age of onset in GBA carriers (heterozygotes) and homozygotes is earlier [47][48][49]. No difference was observed in tremor and dyskinesia between GBA and idiopathic cases in one series [49], although a large European series reported that levodopa induced dyskinesia was more severe in PD with GBA mutations than with controls [48].…”
Section: Motor Featuresmentioning
confidence: 92%
See 1 more Smart Citation